New Method for Nucleophilic Substitution on Hexachlorocyclotriphosphazene by Allylamine Using an Algerian Proton Exchanged Montmorillonite Clay (Maghnite-H+) as a Green Solid Catalyst - Lahouaria Medjdoub; Belbachir Mohammed (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
Nucleophilic substitution on hexachlorocyclotriphosphazene (HCCTP) with allylamine in order to give hexa(allylamino)cyclotriphosphazene (HACTP)  is performed for the first time under mild conditions by using diethylether as solvent to replace benzene which is very toxic. The reaction time is reduced to half and also performed at room temperature but especially in the presence of an eco-catalyst called Maghnite-H+. This catalyst has a significant role in the industrial scale. In fact, the use of Maghnite is preferred for its many advantages: a very low purchase price compared to other catalysts, the easy removal of the reaction mixture. Then, Maghnite-H+ is became an excellent catalyst for many chemical reactions. The structure of HACTP synthesized in the presence of Maghnite-H+ to 5% by weight is confirmed by 1H-NMR, 13C-NMR, 31P-NMR (Nuclear magnetic resonance) and FTIR (Fourier Transform Infrared spectroscopy). MALDI-TOF (Matrix-Assisted Laser Desorption/Ionisation-time-of-flight mass spectrometry) is used to establish the molecular weight of HACTP which is 471 g/mol. DSC (Differential Scanning Calorimetery) and TGA (Thermogravimetric Analysis) show that HACTP is a crystalline product with a melting point of 88 °C. It is reactive after melting but is degraded from 230 °C.